Sustainability. - Halliday, Sandy (RIBA plan of work, 2016)
Sustainability is part of a brand new series providing must-read practical guidance to running efficient and successful projects using the new RIBA Plan of Work 2013. Each guide takes a core project task - in this case those associated with achieving sustainable design and construction - and explains the essential activities required at each stage. Concise and easy to use with a consistent format these guides provide the ultimate quick reference support at your desk or on-site. An authoritative how to' full of pragmatic advice, examples and in-text features such as hints and tips' that illuminate best practice and clever solutions. Designed to be used on all projects - large and small - and across all types of procurement, they are task rather than role-oriented acknowledging that a variety of people take on these responsibilities. They are also invaluable for architectural students at Part 3 who are getting to grips with the realities of practice.